Rpf‐Toxo: A Preliminary Computationally Designed Dense Granule Antigen‐Based Multi‐Epitope Vaccine Against Toxoplasma gondii - Mohamad Hosein Safari; Seyyed Amir Hosseini; Shadan Ghiabi; Shamim Ghiabi; Davood Siamian; Hamidreza Majidiani; Hamid Irannejad; Ali Asghari (Veterinary Medicine and Science, 2026)
ABSTRACT Background Toxoplasma gondii is a protozoan parasite of medical and veterinary importance causing abortion. While current therapies are limited to address the chronic phase of infection, effective prophylactic vaccines are warranted. Objectives In this study, we applied a rational vaccine design approach centred around immunodominant dense granule antigens (GRAs). Methods In silico epitope mapping was performed on six GRAs (GRA15, GRA60, GRA76, GRA83, GRA‐α and GRA‐β). Using web servers, B‐cell, cytotoxic T‐lymphocyte and helper T‐lymphocyte epitopes were predicted and then filtered for antigenicity, solubility and allergenicity. We designed four vaccine constructs by fusing predicted epitopes with specific linkers and adjuvants (RS‐09, RpfE/50S ribosomal protein of Mycobacterium tuberculosis , and human interferon gamma [IFN‐γ]). Constructs were subjected to rigorous evaluation, which included physicochemical evaluation, 3D structural prediction and refinement, toll‐like receptor‐4 (TLR‐4) docking, immune simulation and codon adaptation. Results All candidates exhibited high antigenicity (VaxiJen scores > 0.9) and solubility (> 0.6). Rpf‐Toxo emerged optimal, with non‐allergenic, antigenic (0.9148), soluble (0.658), stable (instability index: 35.41) and hydrophilic (grand average of hydropathicity: −0.641) properties. Docking revealed strong TLR‐4 binding activity (affinity: −20.6 kcal/mol; K d : 7.3e‐16 M) and immune simulation predicted robust responses, including antibody titers > 170,000, Th1‐skewed IFN‐γ (380,000 ng/mL) and memory cell activation; however, these in silico predictions need experimental validation. Codon optimization enhanced expression (CAI: 1.00; GC: 65.63%), and in silico cloning indicated compatibility with pET28a(+). Conclusion These computational predictions require future experimental validation through in vitro and in vivo studies to confirm safety and protective efficacy.